Spectroscopic properties and optoelectronic parameters of ternary composites incorporating poly(L-Tryptophane):P(TER-CO-TRI) and Sudan dye - Rahim, Barham Kamal; Muhammadsharif, Fahmi F.; Saeed, Salah Raza; Ketuly, Kamal Aziz (Journal of Physics: Theories and Applications, 2023)
In this study, the spectroscopic properties and optoelectronic parameters of a ternary composite containing poly(L-Tryptophane): P(TER-CO-TRI) and Sudan dye were thoroughly investigated. Poly(L-Tryptophane) and P (TER-CO-TRI), the electron acceptor and donor, were solution processed and doped with different ratios of Sudan dye to form ternary composite systems. The FTIR technique, UV-Vis spectroscopy, and cyclic voltammetry (CV) were utilized to study the broad properties of the samples. Results showed that with the help of dye doping, the non-dispersive refractive index and energy gap of the ternary system were increased to 2.00 and decreased to 2.11 eV, respectively. The optical band gap, refractive index, dielectric constant, and optical conductivity of the samples were elaborated. The nature of the electronic transition in the studied samples was found to be a direct allowed transition, which was derived from the application of Tauc’s equation. The combination of CV test and absorption spectroscopy was successfully used to determine the molecular energy levels, HOMO and LUMO of the polymer samples.